PENINGKATAN PRODUKSI ASI PADA IBU POST PARTUM MELALUI PIJAT EFFLEURAGE DI KLINIK LMT SIREGAR - Juneris Aritonang; Desideria Yosepha Ginting; Safrina Daulay; Kandace Sianipar (LPPM Universitas Abdurrab, 2022)
Exclusive breastfeeding has a significant effect on the quality of the baby's health. The fact is that only 1 in 2 babies under 6 months are getting exclusive breastfeeding. One way that can affect the increase in breast milk production is by means of massage techniques. This study aims to determine the effectiveness of effleurage massage on breast milk production in post partum mothers This type of research is a quantitative study in the form of a quasi-experimental design with a two-group pretest-posttest design. The population of this study was all post partum mothers who gave birth at LMT Siregar Clinic as many as 14 people and the research sample using accidental sampling technique was 14 people who were divided into 2 groups, intervention and control. Collecting data using observation sheets which were analyzed using the Wilcoxon test. The results showed a p-value of 0.038 in the intervention group and a p-value of 0.083 in the control group. The conclusion is the difference in the production of post partum mother's milk before and after the effleurage massage in the intervention group but there is no difference in the production of breast milk in the control group. For this reason is expected to provide health education on how to increase milk production with effleurage massage techniques and the need to provide support to families to carry out complementary therapy with effleurage massage techniques to increase prolactin hormone levels.